Calcium intake in children aged 9-15 years old - Bahasuan, Haniyah Kamal; Primarti, Risti Saptarini; Indriyanti, Ratna (Universitas Padjadjaran, 2013)
Introduction: Calcium is a main mineral that forms the hard structures of bone and teeth. The Government set standard of calcium intake by Recommended Dietary Allowances (RDA). RDA of children aged 9 years old was 600mg/day and RDA of children aged 10-15 years old was 1000mg/day. The aim of this research was to know about calcium intake in children aged 9-15 years old in Bandung. Methods: The research method was descriptive method with survey technique. Sample selected by cluster random sampling technique, an amount of children of 609 children aged 9-15 years old which was 157 children aged 9 years old and 452 children aged 10-15 years old. Results: The result of this research shows that the average of calcium intake in children aged 9 years old is 435.47 mg/day and children who lack calcium intake is 86 children or 61.43%. The average of calcium intake in children aged 10-15 years old is 613.85 mg/day and children who lack calcium intake is 317 children or 71.72%. Conclusion: Calcium intake in children aged 9-15 years old is less than Recommended Dietary Allowances.